Proyectos para reducir el gasto de la Hacienda española durante el siglo XVIII. Diagnósticos, medidas y resultados en los intentos de hacer menos costosa la Corte - Jurado Sánchez, José (Cuadernos de Estudios Empresariales, 2004)
In this paper plans for cutting down expenditure in the Spanish Treasury during the eighteenth century are studied, specially with regard to the Royal Court. In it are analysed the diagnoses made of the condition of the Exchequer, and measures aimed for improving it, the attempts to reduce the amounts spent by the Court and the results obtained. The conclusions are that the elements that caused the increase in the expenditure are more powerful than the ones that attempted to cut back on this expenditure. Therefore expenditure in the Spanish Household grew notably in the eighteenth century.
Keywords: public expenditure; National Treasury; public sector statistics